Influence of Government Financing on the Performance of TVET Institutions in Kenya - Kigige, Mutembei; Rintari, Nancy; Ongallo, Thomas (International Journal of Professional Practice, 2026)
In the pursuit of improved performance and sustainability, Technical and Vocational Education and Training (TVET) institutions in Kenya increasingly rely on public financing. Government funding plays a critical role in enabling TVET institutions to deliver quality training, enhance infrastructure, and support trainees’ access through capitation and scholarships. Despite ongoing efforts to finance the TVET sector, disparities remain in funding, enrollment and completion rates, and the employability of graduates. This study aimed to investigate the effects of government financing on the performance of TVET institutions in Kenya. A descriptive survey research design was adopted. The main objective was to examine the influence of government financing on the performance of TVET institutions in Kenya. The study targeted TVET institutions within the Mount Kenya East region, and data were collected through a structured questionnaire administered to institutional administrators, teaching staff, and departmental heads. The analysis was conducted using SPSS Version 25, employing both descriptive and inferential statistics, as well as linear regression, to assess the impact of government financing on performance. The findings revealed that government financing significantly contributed to improving the performance of TVET institutions. The study underscores the importance of sufficient, timely, and well-targeted government financing in enhancing the operational effectiveness and performance of TVET institutions.